2022
DOI: 10.3390/molecules27134311
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Molecular Docking Studies of Cu(II), Ni(II), Co(II), and Mn(II) Complexes with Anticonvulsant Therapeutic Agent Gabapentin

Abstract: New Cu(II), Ni(II), Co(II), and Mn(II) complexes of the gabapentin (Gpn) bidentate drug ligand were synthesized and studied using elemental analyses, melting temperatures, molar conductivity, UV–Vis, magnetic measurements, FTIR, and surface morphology (scanning (SEM) and transmission (TEM) electron microscopes).The gabapentin ligand was shown to form monobasic metal:ligand (1:1) stoichiometry complexes with the metal ions Cu(II), Ni(II), Co(II), and Mn(II). Molar conductance measurements in dimethyl-sulfoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The measurement was done in ethanol of 10 –3 M solution at 25 °C. The Λ m values for Mo and Zr complexes are comparatively low (9.7–19.8 Ω –1 cm 2 mol –1 in the case of alloxan complexes), signifying the non-electrolytic manner of these complexes, Table 2 [ 36 ]. However, the molar conductance is of relatively higher values for Fe, Co, Ni, and Cu complexes (49.5–207 Ω –1 cm 2 mol –1 in the case of ninhydrin complexes), supporting the electrolytic property of these complexes and the existence of SO 4 2− and Cl − ions in the outer sphere, Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement was done in ethanol of 10 –3 M solution at 25 °C. The Λ m values for Mo and Zr complexes are comparatively low (9.7–19.8 Ω –1 cm 2 mol –1 in the case of alloxan complexes), signifying the non-electrolytic manner of these complexes, Table 2 [ 36 ]. However, the molar conductance is of relatively higher values for Fe, Co, Ni, and Cu complexes (49.5–207 Ω –1 cm 2 mol –1 in the case of ninhydrin complexes), supporting the electrolytic property of these complexes and the existence of SO 4 2− and Cl − ions in the outer sphere, Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Novel studies have found that antipsychotic drugs transfer positive or negative electrical charges to their substrates, donating or accepting electrons. For example, DA, lithium, clozapine, novel phenothiazines, and aripiprazole give away electrons, preserving the gray matter volume, while most other antipsychotics are electron acceptors and associated with brain volume loss [ 115 , 116 , 117 ]. More studies are needed to identify and develop DA-sparing, electron-donor antipsychotics.…”
Section: Aryl Hydrocarbon the Master Regulator Of Cellular Senescencementioning
confidence: 99%
“…Gabapentin metal complexes (Figure 1) were prepared and fully characterized as discussed in our previous work [22]. The FTIR spectral data of [Mn(Gpn)(H2O)3( Cl…”
Section: Synthesis Of (Gpn) Metal Complexesmentioning
confidence: 99%
“…The molecular docking of gabapentin-cobalt complex has been investigated and gives better activity rather than Gpn [13]. The Mn(II), Co(II), Ni(II) and Cu(II) metal complexes of gabapentin (Gpn), formulized as [Mn(Gpn)(H2O) 2H2O, and [Ni(Gpn)(H2O)3(Cl)].3H2O complexes, have been already synthesized and full characterized in our previous work [22]. In this paper, the quantum chemistry calculations for Gpn and its metal complexes already synthesized were checked using the material studio software as integral applications for published work.…”
Section: Introductionmentioning
confidence: 99%